2017
DOI: 10.1590/1981-863720170002000043137
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Enterococcus faecalis, Staphylococcus warneri and Staphylococcus aureus species in adults with generalized chronic periodontitis

Abstract: Objective To identify and quantify the levels of three bacterial species that have recently been identified as potential "new" periodontal pathogens (Enterococcus faecalis, Staphylococcus aureus and Staphylococcus warneri) in subjects with periodontal health and generalized chronic periodontitis. Methods RESUMOObjetivo Identificar e quantificar os níveis de três espécies bacterianas que foram recentemente apontadas como possíveis "novos" patógenos periodontais (Enterococcus faecalis, Staphylococcus warneri e S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Fritoli et al, 18 who also used the checkerboard technique, found a similar prevalence to Souto et al, 17 with 90% of individuals with PD and 50% of subjects with PH having E. faecalis in their oral cavity. Chidambar et al, 19 using the culture method, found a significant difference in the presence of E. faecalis in individuals with PH (0%) and P (41.7%) in the Indian population.…”
Section: Enterococcus Spp Detectionmentioning
confidence: 58%
See 3 more Smart Citations
“…Fritoli et al, 18 who also used the checkerboard technique, found a similar prevalence to Souto et al, 17 with 90% of individuals with PD and 50% of subjects with PH having E. faecalis in their oral cavity. Chidambar et al, 19 using the culture method, found a significant difference in the presence of E. faecalis in individuals with PH (0%) and P (41.7%) in the Indian population.…”
Section: Enterococcus Spp Detectionmentioning
confidence: 58%
“…32 Besides, the ability of E. faecalis to form biofilm and adhere and invade soft-tissues allows it to survive in many hostile environments such as the periodontal pocket. 33 Fritoli et al 18 showed that the prevalence of E. faecalis was higher in periodontitis patients than in periodontally healthy patients. The same group suggested that there was moderate evidence of the role of E. faecalis as a periodontal pathogen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations